Tłumaczenie dydaktyczne w nauczaniu języka francuskiego na poziomie szkolnym – między teorią a praktyką pedagogiczną (na przykładzie nauczycieli języka francuskiego w województwie śląskim) - Chmiel-Bożek, Halina (Acta Neophilologica, 2020)
Despite the growing number of publications devoted to the potential of translation in modern teaching of foreign languages, in practice pedagogic translation is seen equivocally. This article is an attempt to confront the present-day discourse on pedagogic translation with school practice. Based on the results of a survey con-ducted in the first half of 2019 among teachers of French in the Silesian Voivodeship, the article presents teachers’ opinions on: 1) perceiving pedagogic translation on the basis of knowledge gained during studies and teaching trainings, 2) the purposes of using translations during foreign language classes, and 3) the factors which hinder the introduction of such exercises.